E-GOVERNMENT READINESS IN DEVELOPING COUNTRIES: CHALLENGES AND STRATEGIC PATHWAYS - Nurhamzah; Adzidah; Suryadi (Alqaprint Jatinangor, 2025)
This study explores the multifaceted dimensions of e-government readiness in developing countries through a comprehensive literature review approach. The analysis synthesizes findings from previous empirical and conceptual studies to identify prevailing challenges and strategic pathways toward effective digital governance. Results reveal that limited ICT infrastructure, institutional fragmentation, and inadequate human capital remain critical barriers to e-government implementation. Furthermore, the digital divide and insufficient policy coordination exacerbate disparities in service accessibility and citizen participation. By reviewing scholarly contributions across major databases, the study highlights the need for integrative frameworks that align technology, governance, and social inclusion. Strategic pathways such as capacity building, legal modernization, and multi-stakeholder collaboration are identified as pivotal to enhancing readiness. Comparative insights from successful cases demonstrate the adaptability of global best practices to local contexts. The study contributes to the discourse on digital transformation by offering a synthesized understanding of readiness dynamics in developing nations. It provides actionable recommendations for policymakers to strengthen institutional resilience and promote inclusive digital governance.